Technological and Safety Characterization of Kocuria rhizophila Isolates From Traditional Ethnic Dry-Cured Ham of Nuodeng, Southwest China - Shi, Qiao; Wang, Xinrui; Ju, Zijing; Liu, Biqin; Lei, Changwei; Wang, Hongning; Li, Hong (Frontiers in Microbiology, 2021)
Nuodeng ham is known for its unique processing techniques and flavor. In the present study, proteolytic microorganisms from cured artisanal Nuodeng ham were investigated for starter culture selection. Eight isolates, accounting for 57% of proteolytic microorganisms, were found related to Kocuria rhizophila. Relevant properties of K. rhizophila as potential starter culture were evaluated in vitro for the first time. Intra-species diversities were found in phylogenetic and physiological properties of K. rhizophila isolates. Nevertheless, desirable attributes, such as halo-tolerance, nitrate reductase and protease activity, as well as the absence of antimicrobial resistance and amino acid decarboxylase activity, were observed in selected isolates. Moreover, genome analysis of isolates K24 and K45 confirmed their lack of typical genes for virulence, antimicrobial resistance and amino acid decarboxylase. K. rhizophila may thus represent a novel starter candidate of coagulase-negative cocci group and contribute to color and flavor development of fermented meats.